Cognitive-behavioral approach in Psychotherapy of Children with Specific Isolated Phobias (F40.2) - Fear from Stomatological Treatment - Z. Kolařík; K. Nováková; P. Němečková (Czech Dental Chamber, 2006)
The aim of the authors was to draw attention to the possibility of treating non-collaborating children, especially if the problem behavior is an isolated phobia from stomatological treatment, using the team collaboration of a stomatologist, psychologist and pediatric psychiatrist. The presented individual psychotherapeutic approach - cognitive behavioral psychotherapy - is more acceptable for the child, safer, more considerate, without side effects, frequently also with a long-lasting effect and less frustrating for the parents. The patients with dental phobia are frequently taken care of in general anesthesia.The stress from stomatological treatment belongs to frequent causes of problem treatment of children. In some children the cause of inadequate behavior is associated with a certain tool used in a stomatological office (injection syringe, extraction forceps), in other children to procedures during the treatment (preparation, extraction). If we can eliminate the feared of tools or substitute them with another solution or to use psychotherapy knowledge and skills, the stomatologist can deal with this problem. In case of failure the only solution is to perform the treatment, often repeatedly, in general anesthesia. The minimizing of the phobia is in the hands of specialists - a psychologist and children psychiatrist.The authors refer to a successful management of dental phobia in children less than three years old by means of an individual psychotherapeutic approach - a cognitive behavioral psychotherapy. This method is based on proved scientific approaches and built on experience of precise description of the symptoms or problems, which should be influence by the therapeutic procedure (including their frequency, severity and dependence on specific situations). It is based on s skilled use of elaborated and verified techniques in a fixed structure of individual therapeutic "sessions". One of behavioral mediation models, theoretically based on a systematic desensitization according to Josef Wolpe, is the theory of reciprocal inhibition - i.e. connection of an unpleasant stimulus with a pleasant situation (a relaxed state etc.). The neurotic behavior is usually acquired in situations arousing fear or anxiety. The treatment represents an attempt of reciprocal inhibition of neurotic reactions. The inhibition of anxiety reactions is evoked by simultaneous induction of other reactions, which are incompatible with fear from the physiological point of view and thereby diminishing undesirable conditional connections between this stimulus and fear. The systematic desensitization is based on counter-conditioning.The authors describe the procedure in psychological examination and in detail and comprehensively individual psychotherapy procedures in individual treated children.The first two female patients treated by the stomatologist during hospitalization at the Children Ward of the Psychiatric Clinic, Medical Faculty UP and Faculty Hospital, the third female patient was dentally treated after outpatient psychological preparation with the care of an educated and supporting mother. The stomatological treatment with subsequent dental reconstruction was performed in the presence and under psychological guidance of the care taking psychologist in a stomatological consult